School Management’s Control Over Students in Street Racing Cases - Dinda Yulia; Kasmanto Rinaldi (International Conference On Law And Social Sciences, 2024)
Street racing is a common activity among teenagers in Pekanbaru, Riau Province. This is undoubtedly due to the social interactions among teenagers and their choice of peers. Additionally, the impact of parental communication patterns with their children is highly relevant when associated with the daily lives and activities of children within their social environment. Street racing involves reckless motorcycle speeding on public roads, with the risk of fatal accidents occurring for both the teenagers engaged in street racing and other road users. Those involved in street racing activities are often students in schools. Therefore, there is a need for intervention or control from the school authorities regarding the frequent occurrences of street racing incidents. In this context, the researcher aims to explore further how schools handle cases of teenage delinquency, particularly in street racing incidents. The research method employed here is qualitative. The findings of this research conclude that the school authorities have implemented control measures concerning street racing incidents involving students at Senior High School 15 Pekanbaru, (SMA N 15 Pekanbaru), by providing education, guidance, and sanctions to prevent students from engaging in deviant behavior, especially street racing, which is prevalent in the city of Pekanbaru. Keywords: Control, juvenile delinquency, street racing